Asexual micromycetes found on Quercus spp. (Fagaceae) leaves from Huixquilucan, Mexico State, Mexico - Delgado Zúñiga, José Pablo; Heredia, Gabriela; Rodríguez-Gutiérrez, Ibeth (Instituto de Ecología, A.C., 2022)
Background and Aims: Asexual micromycetes (AM) are a diverse and abundant group of fungi in nature. Until now the AM had not been studied in the natural areas of Mexico State. The aim of this contribution is to provide information on the AM species richness on senescent living leaves and decomposing leaves on the ground of five species of Quercus from a temperate forest in the municipality of Huixquilucan in Mexico State, Mexico.Methods: During one year, every two weeks, samples of mature living leaves were cut from five oak species, and dead leaves were collected from the ground. Samples were incubated in moist chambers. Microscopic examination was carried out twice a week. Taxonomic determinations were based on conidiogenesis and on morphometric characters of the conidiomata. Reference material (microscopic slides) was deposited in the herbarium of the Instituto de Ecología, A.C. (XAL) in Xalapa, Veracruz, Mexico. The new records for the mycobiota from Mexico are illustrated and described in detail.Key results: Thirty AM species were determined; 12 were not known from Mexico, and all of them are new records for Mexico State. More species were found on the decaying leaves on the ground than on senescent living ones. Eight species of AM had not been collected since they were described as new species for science. Trichothecium roseum, Pestalotiopsis maculans and Vermiculariopsiella immersa are widely distributed micromycetes on the leaves of all the studied oaks.Conclusions: The richness of AM species found in the study area shows that Quercus leaves are substrates that harbor a considerable fungal richness, largely unknown in Mexico. This is an important reason for the conservation of Quercus forests and promoting studies on AM in our country.